Integrability for Solutions of Anisotropic Obstacle Problems - Hongya Gao; Yanjie Zhang; Shuangli Li (International Journal of Mathematics and Mathematical Sciences)
This paper deals with anisotropic obstacle problem for the 𝒜-harmonic equation ∑i=1nDi(ai(x,Du(x)))=0. An integrability result is given under suitable assumptions, which show higher integrability of the boundary datum, and the obstacle force solutions u have higher integrability as well.